Image Experience and Sound Density: - Ana Cristina Moreira Pessôa (Revista Brasileira de Estudos da Presença)
This article proposes to problematize notions of presence and body from the sound dimension in a performance of the opera Auto da Catingueira, by Elomar Figueira Mello. The study uses a bibliographical, critical and theoretical review, and discusses parts of the recording of the spectacle in close dialogue with music theory and concepts brought from oral poetics. Thus, an analysis of the elements of the performance of actors in the scenic phenomenon is presented in relation to concepts of orality, body and voice, bringing together aspects of performativity and staging based on Brazilian culture and popular actions.